The Challenges of Saving Mothers from Childbirth-Related Injuries and Deaths in Nigeria - James, Godswill (Richtmann Publishing, 2013)
Nigeria’s national maternal mortality rate is estimated at 545 per 100,000 live births in 2008. Despite the decrease compared toprevious rate of 800 per 100,000 live births in 2005 it is still high, and presents a picture of maternal health status of thecountry. Nigerian government has embarked on programmes to reduce maternal mortality such as, Midwife Service Scheme(MSS) aimed at achieving the fifth Millennium Development Goals (MDG) for increased maternal health and survival. However,the achievement made so far is low as annual percentage decline in maternal mortality ratio from 1990-2008 was 1.5%compared to the targeted 5.5%. In addition, maternal deaths and lifetime risk is high as a woman’s chance of dying frompregnancy and childbirth in Nigeria is 1 in 13, while it is 1 in 5000 in developed nations. Against the backdrop of the worseningstate of maternal health in Nigeria, this paper examines the crucial challenges militating against efforts at saving mothers fromchildbirth-related injuries and death in Nigeria. Relying mainly on secondary data, the author contends that maternal health is afunction of significant and complex underlying interaction of socio-cultural and environmental factors. It is argued that socioculturalcontext within which Nigerian people live affects their ideas, decisions and behavior concerning maternal deaths; itaffects what people know about pregnancy and delivery, what preparations they make and what they do about life-threateningcomplications and it ultimately poses challenges on maternal health in Nigeria.